2011
DOI: 10.1289/ehp.1003391
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene Reduces Testosterone Production in Rat Leydig Cells via a Direct Disturbance of Testicular Steroidogenic Machinery

Abstract: Background: Benzo[a]pyrene (B[a]P), a polycyclic aromatic hydrocarbon (PAH), is a ubiquitous environmental pollutant that is currently suspected of being an endocrine disruptor. The testis is an important target for PAHs, yet insufficient attention has been paid to their effects on steroidogenesis in Leydig cells.Objective: We hypothesized that long-term exposure to low concentrations of B[a]P might disrupt testosterone production in Leydig cells via an alteration of steroidogenic proteins.Results: Oral exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…Recently, however, a potent endocrine disrupting mechanism of testosterone production was proposed in Leydig cells after exposure to B[a]P (Chung et al, 2011 …”
Section: Reduction Of Testosterone Production In Leydig Cells By Pahsmentioning
confidence: 99%
“…Recently, however, a potent endocrine disrupting mechanism of testosterone production was proposed in Leydig cells after exposure to B[a]P (Chung et al, 2011 …”
Section: Reduction Of Testosterone Production In Leydig Cells By Pahsmentioning
confidence: 99%
“…The reduced transcription arises at very low in ovo doses of estrogens and was observed in male hatchlings exposed to o,p' -sist into adulthood (Kamata et al, 2009a(Kamata et al, , 2009b. p,p'-DDT, but not p,p'-DDE, conversely upregulated transcription of the CYP11A1 gene even at the lowest dose CYP11A1 was reported in the ovary and testis of fathead minnows (Pimephales promelas) exposed for 4 days to prochloraz, a fungicide which acts as an aromatase inhibitor and anti-estrogen, and in the testis of rats orally exposed to benzo[a]pyrene (B[a]P) for 90 days (Ankley et al, 2009;Chung et al, 2011). In female fathead minnows transcriptions of the cyp19a1a, cyp17 and follicle stimulating hormone receptor (fshr) genes increased at the same time, and in B[a]P exposed rats serum and pituitary gland levels of luteinizing hormone (LH) increased.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of testosterone production has been extensively reported [4,5,6,7,8,9,10,11]; Leydig cells are responsible for the production of the testicular androgen testosterone in the mammalian testis. A previous report showed that decreased testosterone production in Leydig cells leads to decrease in serum testosterone levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous report showed that decreased testosterone production in Leydig cells leads to decrease in serum testosterone levels [7]. Testosterone biosynthesis in these cells is induced by stimulation with gonadotropin luteinizing hormone (LH).…”
Section: Introductionmentioning
confidence: 99%